The impact of regional deprivation and individual socio‐economic status on the prevalence of Type 2 diabetes in Germany. A pooled analysis of five population‐based studies. Issue 3 (20th February 2013) - Maier, W.; Holle, R.; Hunger, M.; Peters, A.; Meisinger, C.; Greiser, K. H.; Kluttig, A.; Völzke, H.; Schipf, S.; Moebus, S.; Bokhof, B.; Berger, K.; et al.
Abstract Aim Our objective was to test the hypothesis that the prevalence of Type 2 diabetes increases with increasing regional deprivation even after controlling for individual socio‐economic status. Methods We pooled cross‐sectional data from five German population‐based studies. The data set contained information on n = 11 688 study participants (men 50.1%) aged 45–74 years, of whom 1008 people had prevalent Type 2 diabetes (men 56.2%). Logistic multilevel regression was performed to estimate odds ratios (OR) and 95% confidence intervals (CI) for diabetes prevalence. We controlled for sex, age and lifestyle risk factors, individual socio‐economic status and regional deprivation, based on a new small‐area deprivation measure, the German Index of Multiple Deprivation. Results Adjusted for sex, age, body mass index (BMI), physical activity, smoking status and alcohol consumption, the prevalence of Type 2 diabetes showed a stepwise increase in risk with increasing area deprivation [OR 1.88 (95% CI 1.16–3.04) in quintile 4 and OR 2.14 (95% CI 1.29–3.55) in quintile 5 compared with the least deprived quintile 1], even after controlling for individual socio‐economic status. Focusing on individual socio‐economic status alone, the risk of having diabetes was significantly higher for low compared with medium or high educational level [OR 1.46 (95% CI 1.24–1.71)] and for the lowest compared with the highest income group [OR 1.53 (95% CI 1.18–1.99)]. Conclusion Regional deprivation plays a significant part in the explanation of diabetes prevalence in Germany independently of individual socio‐economic status. The results of the present study could help to target public health measures in deprived regions.